4-Hydroxynonenal induces p53-mediated apoptosis in retinal pigment epithelial cells - Sharma, Abha (2008)
4-Hydroxynonenal (4-HNE) has been suggested to be involved in stress-induced signaling for apoptosis. In present studies, we have examined the effects of 4-HNE on the intrinsic apoptotic pathway associated with p53 in human retinal pigment epithelial (RPE and ARPE-19) cells. Our results show that 4-HNE causes induction, phosphorylation, and nuclear accumulation of p53 which is accompanied with down regulation of MDM2, activation of the pro-apoptotic p53 target genes viz. p21 and Bax, JNK, caspase3, and onset of apoptosis in treated RPE cells. Reduced expression of p53 by an efficient silencing of the p53 gene resulted in a significant resistance of these cells to 4-HNE-induced cell death. The effects of 4-HNE on the expression and functions of p53 are blocked in GSTA4-4 over expressing cells indicating that 4-HNE-induced, p53-mediated signaling for apoptosis is regulated by GSTs. Our results also show that the induction of p53 in tissues of mGsta4 (-/-) mice correlate with elevated levels of 4-HNE due to its impaired metabolism. Together, these studies suggest that 4-HNE is involved in p53-mediated signaling in in vitro cell cultures as well as in vivo that can be regulated by GSTs.